2016
DOI: 10.4103/0972-4052.191289
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary sinus augmentation using sinus membrane elevation without grafts - A Systematic Review

Abstract: Implants have a predictable outcome and are the foremost treatment modality for prosthetic rehabilitation of edentulous patients. Due to loss of bone after extraction and pneumatization of maxillary sinus, there is insufficient bone volume for implant placement. The direct maxillary sinus lift procedure has been performed with different grafting materials (autogenous bone grafts, alloplasts, allografts, and xenografts) and without grafting material, having new bone formation around the implant. There is no evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…GBR-MSA has been performed using a number of grafting materials, including autologous bone grafts, allografts, and xenografts[106]. An earlier meta-analysis published in 1998 found that the survival rates of implants placed in grafted maxillary sinuses did not depend on whether autologous, allogeneic, or alloplastic grafts were used[107].…”
Section: Discussionmentioning
confidence: 99%
“…GBR-MSA has been performed using a number of grafting materials, including autologous bone grafts, allografts, and xenografts[106]. An earlier meta-analysis published in 1998 found that the survival rates of implants placed in grafted maxillary sinuses did not depend on whether autologous, allogeneic, or alloplastic grafts were used[107].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, initially we analyzed the implant survival rate (ISR) within non-grafted TSFE studies among different RBH, and no significant differences were observed on 1-year ISR among groups with different average RBH within non-grafted TSFE group, even cases with limited RBH (<4 mm) obtained favorable 1-year ISR 51,60,61 . This confirmed that limited RBH does not impact the implant survival for non-grafted TSFE surgeries, as long as secured primary stabilities are obtained on implants 51,60,61 . Furthermore, the increase in bone-implant contact area and the compression of bone during TSFE augments the bone density around implant sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, this procedure has several disadvantages and limitations such as the success and predictability of this protocol relies on the handling, blood collection time and its transference for the centrifuge, the patient may refuse the puncture required for blood collection, rigidity lack and fast degradation of the PRF, the size of the defect and amount of bone loss. [ 15 16 ]…”
Section: Discussionmentioning
confidence: 99%